Impact of the information and communication infrastructure on manufacturing trade - Bojnec, Štefan (Advances in business related scientific research journal, 2010)
We investigate the impact of the information and communication infrastructure development (ICID) on the patterns of bilateral manufacturing trade between the developed OECD countries. More developed information and communication infrastructure provides externalities for the bilateral manufacturing trade due to a reduction in information and communication costs. We employ adapted gravity trade equations to identify the effects of the ICID on bilateral manufacturing trade. The ICID is positively associated with manufacturing trade for exporting countries, while results for importing countries are mixed. The sensitivity of the results is investigated, and the model is re-estimated estimating for the effect of the ICID on distance. The ICID causes to overcome the effects of the distance on manufacturing exports and strengthened import specialization. Gross domestic product positively effects manufacturing trade for exporters and importers. The distance cause negatively, while having a common language and regional free trade agreement membership cause positively manufacturing trade between the eighteen analyzed OECD countries.
Keywords: adapted gravity model; communication; države OECD; informacije; information; international trade; komuniciranje; manufacturing; mednarodna trgovina; modeli; OECD coutries; proizvodnja